2016
DOI: 10.1016/j.fertnstert.2015.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Microdose flare protocol with interrupted follicle stimulating hormone and added androgen for poor responders—an observational pilot study

Abstract: The androgen-interrupted FSH protocol may improve follicular response to gonadotropins in cycles that might otherwise be cancelled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Reports have also assessed the efficacy of administering the bioactive androgen, testosterone, in POR patients to improve ovarian response and IVF outcomes (Table 3). Although four RCTs (two with placebo controls) assessing the impact of transdermal testosterone administration for 5-20 days in POR patients showed no significant effect of testosterone pre-treatment (Massin et al 2006, Fabregues et al 2009, Sipe et al 2010, Bosdou et al 2016, since then numerous studies, including a placebo-controlled RCT, have reported on a range of beneficial effects of pre-IVF testosterone pre-treatment (Balasch et al 2006, Kim et al 2011, Mitri et al 2016, Doan et al 2017, Saharkhiz et al 2018. These beneficial effects include improved antral follicle numbers, oocyte retrieval numbers, fertilization rates, embryo implantation rates, embryo quality, clinical pregnancy rates and live birth rates in some women (observations from studies summarized in Table 3).…”
Section: Testosteronementioning
confidence: 99%
“…Reports have also assessed the efficacy of administering the bioactive androgen, testosterone, in POR patients to improve ovarian response and IVF outcomes (Table 3). Although four RCTs (two with placebo controls) assessing the impact of transdermal testosterone administration for 5-20 days in POR patients showed no significant effect of testosterone pre-treatment (Massin et al 2006, Fabregues et al 2009, Sipe et al 2010, Bosdou et al 2016, since then numerous studies, including a placebo-controlled RCT, have reported on a range of beneficial effects of pre-IVF testosterone pre-treatment (Balasch et al 2006, Kim et al 2011, Mitri et al 2016, Doan et al 2017, Saharkhiz et al 2018. These beneficial effects include improved antral follicle numbers, oocyte retrieval numbers, fertilization rates, embryo implantation rates, embryo quality, clinical pregnancy rates and live birth rates in some women (observations from studies summarized in Table 3).…”
Section: Testosteronementioning
confidence: 99%
“…Of these, 936 records were excluded after title/ abstract screening (not relevant to the review). We examined the full text of 18 remaining manuscripts, and, of these, we excluded 10 papers-one paper due to the lack of data concerning CPR and/or LBR [27], one trial reported data not analyzable [28], three papers because the design was observational [29][30][31], and six papers because they were review/metaanalysis [11-13, 21, 32, 33]. Finally, 7 manuscripts were included in the meta-analysis [10,[22][23][24][34][35][36].…”
Section: Study Selectionmentioning
confidence: 99%
“…A poor response to ovarian stimulation is not common, and presents a significant therapeutic challenge. Many approaches have been proposed to improve clinical outcomes of PORs, including a modified ovarian stimulation protocol (7,8), androgen treatment (9,10), and a stem cell ovarian transplant (11).…”
Section: Introductionmentioning
confidence: 99%